Group 2 Innate Lymphoid Cells Exhibit Tissue-Specific Dynamic Behaviour During Type 2 Immune Responses - Lok, Laurence S. C.; Walker, Jennifer A.; Jolin, Helen E.; Scanlon, Seth T.; Ishii, Masaru; Fallon, Padraic G.; McKenzie, Andrew N. J.; Clatworthy, Menna R. (Frontiers in Immunology, 2021)
Group 2 innate lymphoid cells (ILC2s) are early effectors of mucosal type 2 immunity, producing cytokines such as interleukin (IL)-13 to mediate responses to helminth infection and allergen-induced inflammation. ILC2s are also present in lymph nodes (LNs) and can express molecules required for antigen presentation, but to date there are limited data on their dynamic behaviour. We used a CD2/IL-13 dual fluorescent reporter mouse for in vivo imaging of ILC2s and Th2 T cells in real time following a type 2 priming helminth infection or egg injection. After helminth challenge, we found that ILC2s were the main source of IL-13 in lymphoid organs (Peyer’s patches and peripheral LNs), and were located in T cell areas. Intravital imaging demonstrated an increase in IL-13+ ILC2 size and movement following helminth infection, but reduced duration of interactions with T cells compared with those in homeostasis. In contrast, in the intestinal mucosa, we observed an increase in ILC2-T cell interactions post-infection, including some of prolonged duration, as well as increased IL-13+ ILC2 movement. These data suggest that ILC2 activation enhances cell motility, with the potential to increase the area of distribution of cytokines to optimise the early generation of type 2 responses. The prolonged ILC2 interactions with T cells within the intestinal mucosa are consistent with the conclusion that contact-based T cell activation may occur within inflamed tissues rather than lymphoid organs. Our findings have important implications for our understanding of the in vivo biology of ILC2 and the way in which these cells facilitate adaptive immune responses.